Correction of the CSA does not decrease the re-tear rate after SSP repair - Lücke, Christoph; Schnetzke, Marc; Bruttel, Jennifer; Storg, Janis; Loew, Markus; Lichtenberg, Sven (Obere Extremität, 2021)
The re-tear rate after supraspinatus tendon (SSP) repair is high despite optimization of surgical techniques. The critical shoulder angle (CSA)> 35° has been identified as a risk for re-tear. Surgical reduction of the CSA performing additional lateral acromioplasty (ALAP) is intended to reduce the risk.
Gesehen am 11.04.2023